Relationship between social support and family caregiver burden in schizophrenia patients - Sustrami, Dya; Yusuf, Ah; Fitryasari, Rizki; Efendi, Ferry; Aysha, Riski Firlana (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the impact of social support on family caregivers of schizophrenia patients. Method: The cross-sectional, observational study was conducted at Menur Mental Health Hospital, Surabaya, Indonesia, from June to July 2021, and comprised family caregivers aged 20-60 years who lived with schizophrenia patients. Data was collected using the Indonesia version of Zarit Burden Interview and the social support questionnaire. Data was analysed using SPSS 25. Results: Of the 160 subjects, 87(54.4%) were males and 73(45.6%) were females, and 88(55%) were adults, while 36(22.5%) had duration of care >10 years. All the 160(100%) patients had been receiving regular treatment. There were 64(40%) respondents who reported having good social support. The correlation between social support and the family caregiver burden related to schizophrenia patients was significant (p< 0.05). Conclusion: There was a significant relationship between social support and burden on family caregivers of schizophrenia patients. Keywords: Caregiver, Schizophrenia, Burden, Psychiatric, Ambulatory care.